Towards a Framework for the Monitoring and Evaluation of Collaborative Learning Health Systems - Espadero, Mary Cathryn (Université d'Ottawa | University of Ottawa, 2025)
This scoping review aimed to explore how Collaborative Learning Health Systems (CLHSs) are being monitored and evaluated. The research questions are: (1) “What dimensions are used to monitor and evaluate CLHSs?” and (2) “What metrics are used to operationalize the dimensions for monitoring and evaluating CLHSs?” A search strategy was applied to multiple databases, LHS scoping reviews, and reference lists of included records. Records focused on CLHS monitoring and evaluation studies, frameworks, and tools were included. Thematic analysis, informed by a performance measurement lens, was conducted to synthesize and organize the results. Among the 1,122 records screened, there were 45 records included in the analysis. The results were synthesized into 24 dimensions and grouped into six perspectives: Enablers, Collaboration, Practice to Data, Data to Knowledge, Knowledge to Action, and Health System Outcomes. There were 20 frameworks and tools that were proposed or used by the records to monitor and evaluate CLHSs. Most of them were only used once, indicating that there has yet to be a dominant or widely used CLHS monitoring and evaluation framework. The dimensions identified in this study are more comprehensive than those in the included frameworks and more tailored to CLHS needs than existing LHS or performance measurement frameworks. To illustrate how these results can be used, they were applied to an existing CLHS, RESPECT. This study provides a foundation for further empirical research toward developing a CLHS monitoring and evaluation framework. Advancing this research can guide healthcare leaders and researchers in planning, monitoring, and evaluating CLHSs.
Keywords: learning health system; evaluation; performance measurement